Newton's Law Learning Transformation: Interactive Android Application with Adobe Flash Professional CS6 - Haj, Mochammad Irsyadul; Fauzi, Ahmad; Budiawanti, Sri (Jurnal Materi dan Pembelajaran Fisika, 2024)
This study describes the product specifications and user assessment of Android-based physics learning media using Adobe Flash Professional CS6 with a scientific approach to Newton's Law material that is well-criteria in language, material, and media. This research and development uses a qualitative descriptive analysis approach developed by Branch (2009). Data analysis uses analysis techniques developed by Azwar (2007). The procedure for making this learning media is to Analyze, Design, and Develop. The results of this study are in the form of a learning media with (1) Physics learning media made is an android application-based learning media with the extension Application Package (.apk) with minimum specifications OS (Operating System) android v 7.0 Nougat, Snapdragon 435 chipset and CPU Octa-core Max 1.40GHz, with a minimum of having 2 GB RAM, 2 GB ROM, and 480 x 800 resolution. Physics learning media based on the material and lesson plans of Newton's Law material with a scientific approach. Physics learning media contains Learning, Material, Evaluation, and Settings pages with features such as simulation, movie clips, video, UI, scrolling text, swipe gallery, drag and drop, sound, and without internet (offline). (2) The physics learning media made has a validation value on the basha aspect of 43, the material of 71, and media 71, so the learning media validation value is 185 with a very good category. The physics learning media has an assessment response value from 3 teachers, namely 100% of teachers stated very well, and the assessment response value from 30 students, namely, 23% of students stated in the good category and 77% stated in the very good category. This research can be the basis for developing interactive android application with Adobe Flash Professional CS6 for Newton's Law material.